Methodological approaches to economic and mathematical modelling of crop rotation in the development of a land management project that provides ecological and economic justification for crop rotation - Dorosh, Y.; Ibatullin, Sh.; Dorosh, O.; Dorosh А.; Sakal, O. (Land Management, Cadastre and Land Monitoring, 2024)
The proposed research paper systemises methodological approaches to optimisation and dynamic modelling of crop rotation in the development of land management projects that provide ecological and economic justification of crop rotation, since the crop rotation models proposed to date do not solve the task in general, but only in certain specific cases. In this regard, the need to develop full-fledged software products with a user interface integrated into existing information and accounting databases of agricultural formations is substantiated. It is proved that economic and mathematical modelling of crop rotations should be developed by improving the methodology of dynamic crop rotations, which will allow farmers to analyse the economic efficiency of various alternative options for crop rotation under specific natural and economic conditions and constraints, as it is a promising interactive tool for substantiating management production decisions based on optimisation algorithms and analysis of large amounts of accumulated retrospective data. The approaches, criteria and limitations of the economic and mathematical model of crop rotation in the development of land management projects that provide ecological and economic justification of crop rotation are substantiated. The proposed economic and mathematical model with its objective function, constraints and algorithms is aimed at a comprehensive solution of issues related to production planning and rational land use. The presented model provides ample opportunities for further optimisation of the system of making effective managerial decisions in the agricultural sector and can serve as a basis for solving the problems of investment justification and development of agricultural land use.